Effect of Combining Resistance Training and Curcumin Supplementation on Lipid Profile in Obese Women - Zohre Amirkhani; Mohammad Ali Azarbayjani; Maghsoud Peeri; Hasan Matin Homaei (Mashhad University of Medical Sciences, 2017)
Introduction: According to the relationship between the lifestyle, health and non-transmitted diseases, changing the pattern of lifestyle can have positive effects on health. However, the effect of lifestyle and the incidence of diseases caused by obesity and its related disorders are not well known. Therefore, this study was performed with aim to evaluate the effect of combining resistance training and curcumin usage on lipid profile in inactive overweight and obese women. Methods: This randomized clinical trial was performed at second semester of the academic year of 2013-2014 on 40 students (from the Islamic Azad University of Mashhad) of inactive women at age range of 20-35 years and healthy with cholesterol close to the risk domain and BMI: 28-32 kg/m2. The subjects were randomly divided into four groups of 10 cases: control, training-placebo, curcumin, and training-placebo. The group of curcumin consumed 80 mg Nano-micelles curcumin/day for 8 weeks. The training groups also performed resistance training three sessions per week for a total of eight weeks. Data on lipid profile were collected using blood tests. Data were analyzed using SPSS software (version 18), and variance analysis, Kruskal-Wallis, Covariance analysis and Scheffe test. P<0.05 was considered significant. Results: After eight weeks of exercise, serum concentration of triglycerides significantly decreased in the group of training in combination with curcumin compared to the curcumin group (p =0.027) with group. No significant difference was observed in the concentration of VLDL-c (P= 0.389), HDL-c, (p=0.205), LDL-c (p=0.503) and cholesterol (p=0.335) after combining resistance exercise and using curcumin. Conclusion: Resistance training and curcumin do not reinforce each other's effect on reducing lipid profile. The response of lipid profile to training and curcumin was not similar. According to this, both training and consumption curcumin and their combination on some lipid profile indicators had a desirable effect, recommended that overweight girls use preventive measures for each of these interventions.